The New Trend in Development of The Textbook for Writing Based on The Integrative Approach for College Students in Indonesia - Kristina Imron (UIN Sunan Gunung Djati Bandung, 2023)
The objectives of this study are: (1) to develop a textbook for the subject of writing skills based on an integrative approach, (2) to conduct a formative evaluation on the use of the textbook developed at Arabic Teaching Department at Raden Fatah Islamic State University in Palembang. The research method used is R&D research with Borg and Gall models and the instructional design models based on the Dick and Carry system adapted and modified by the researcher. The methods used to collect data are questionnaires, documentation, interview, pre-test, post-test, and comparing the results of the two tests using the SPSS calculation system. The results of the study comprise the following: (1) The textbook product of writing skills based on an integrative approach includes ten chapters, and each chapter contains five integrated materials: (a) reading; (b) dictation; (c) morphology, (d) grammar, and (e) writing skill. (2) Formative evaluations state that the results of the small group experiments indicate the higher scores of the participants' learning outcomes that show that the post-test deviations of 3.2 and the deviations of the pre-test of 2.9 means that the mean of 88.2 shows an improvement compared to the results of the pre-test which is 65.4, which means that there is an improvement of the learning abilities of the trial participants in the small groups.